2023
DOI: 10.1097/hrp.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter-2 Inhibitors in Depression

Abstract: Novel treatment strategies that refract existing treatment algorithms for depressive disorders are being sought. Abnormal brain bioenergetic metabolism may represent an alternative, therapeutically targetable neurobiological basis for depression. A growing body of research points to endogenous ketones as candidate neuroprotective metabolites with the potential to enhance brain bioenergetics and improve mood. Sodium-glucose cotransporter-2 (SGLT2) inhibitors, originally approved for the treatment of diabetes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…Fourth, our metaanalysis identified that SGLT2is were associated with lower incidences of aphasia and mental status changes. Meanwhile, Liebers et al proposed the hypothesis that ketogenesis induced by SGLT2is could be an effective treatment for depressive disorders (37). Fifth, our meta-analysis identified that SGLT2is were associated with a lower incidence of anemia.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Fourth, our metaanalysis identified that SGLT2is were associated with lower incidences of aphasia and mental status changes. Meanwhile, Liebers et al proposed the hypothesis that ketogenesis induced by SGLT2is could be an effective treatment for depressive disorders (37). Fifth, our meta-analysis identified that SGLT2is were associated with a lower incidence of anemia.…”
Section: Discussionmentioning
confidence: 70%
“…Meanwhile, Liebers et al. proposed the hypothesis that ketogenesis induced by SGLT2is could be an effective treatment for depressive disorders ( 37 ). Fifth, our meta-analysis identified that SGLT2is were associated with a lower incidence of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have increasingly highlighted the neuroprotective effects of SGLT2 inhibitors. Population‐based studies suggest that SGLT2 inhibitors are associated with a decreased risk of dementia and depression (Liebers et al., 2023 ; Wu et al., 2023 ). Preclinical experiments have shown that these medications can improve brain energetics (Pawlos et al., 2021 ), and a recent randomized controlled trial demonstrated improved mood outcomes with the selective SGLT2 inhibitor empagliflozin in combination with citalopram (Zandifar et al., 2024 ).…”
Section: Introductionmentioning
confidence: 99%